Mycobacterium tuberculosis Thymidylyltransferase RmlA Is Negatively Regulated by Ser/Thr Protein Kinase PknB - Qu, Dehui; Zhao, Xiaohui; Sun, Yao; Wu, Fan-Lin; Tao, Sheng-Ce (Frontiers in Microbiology, 2021)
Ser/Thr phosphorylation by serine/threonine protein kinases (STPKs) plays significant roles in molecular regulation, which allows mycobacteria to adapt their cell wall structure in response to the environment changes. Identifying direct targets of STPKs and determining their activities are therefore critical to revealing their function in mycobacteria, for example, in cell wall formation and virulence. Herein, we reported that RmlA, a crucial L-rhamnose biosynthesis enzyme, is a substrate of STPK PknB in Mycobacterium tuberculosis (M.tb). Mass spectrometry analysis revealed that RmlA is phosphorylated at Thr-12, Thr-54, Thr-197, and Thr-12 is located close to the catalytic triad of RmlA. Biochemical and phenotypic analysis of two RmlA mutants, T12A/T12D, showed that their activities were reduced and cell wall formation was negatively affected. Moreover, virulence of RmlA T12D mutant was attenuated in a macrophage model. Overall, these results provide the first evidence for the role of PknB-dependent RmlA phosphorylation in regulating cell wall formation in Mycobacteria, with significant implications for pathogenicity.